Linking major shifts in East Africa 'short rains' to the Southern Annular Mode. (6th August 2015) - Manatsa, Desmond; Mudavanhu, Chipo; Mushore, Terrence D.; Mavhura, Emmanuel
ABSTRACT: The Southern Annular Mode (SAM) is a natural climate mode of variability whose discovery can be traced back at least as far as the beginning of the 20th century, before human activities produced enough gases to noticeably change the climate. However, recent observed changes in the SAM are linked to increases of greenhouse gases and stratospheric ozone depletion, hence assigning SAM's alterations, in large part, to human activities. In this study, the 20th century reanalysis data were used to establish the SAM's prominent shifts during the years 1917, 1961 and 1997. The first shift coincides with abrupt greenhouse gas increases and the latter shifts are attributed to stratospheric ozone level changes. The East Africa 'Short Rains' (EASR) index derived from the Global Precipitation Climatology Center (GPCC) dating back to the beginning of the 20th century, demonstrates coinciding shifts with the SAM index. However, the SAM's influence on EASR appears to be achieved through a meridional dipole that is formed in the sea‐level pressure of the Indian Ocean basin, with one pole over the Tropics and the other over the extratropics. When this dipole pattern is weakly developed as the period between 1961 and 1997, the SAM is decoupled from the EASR and the Indian Ocean Dipole (IOD) demonstrates a dominant role in modulating the EASR. The SAM is also linked to the IOD through its control of the Mascarene High variability, hence connecting the SAM to the dominant circulation variability in the Indian Ocean. Although the El Nino Southern Oscillation is strongly correlated to EASR, it is not related to the epochal variability in the rainfall. Therefore, the slow modulation in EASR is linked to the SAM whose shifts are triggered by gases emanating from human influences.